Attitudinal Stance and Code-Switching as Persuasive Tools in Malaysian Digital Activism: A Corpus-Assisted Discourse Analysis of Mobilisation Discourse - Habibah Ismail; Nurshafawati Ahmad Sani (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2026)
Tier 2 (Indexed by ISI and Scopus)